Flow cytometric analysis of conjunctival epithelium in ocular rosacea and keratoconjunctivitis sicca - Pisella, Pierre-Jean; Brignole, Françoise; Debbasch, Caroline; Lozato, Paul-Alexandre; Creuzot-Garcher, Catherine; Bara, Jacques; Saiag, Philippe; Warnet, Jean-Michel; Baudouin, Christophe (Ophthalmology (Rochester, Minn.), 2000)
To investigate by flow cytometry and impression cytology (IC) specimens the inflammatory status of the conjunctival epithelium and goblet cell density in two series of patients with rosacea and dry eye syndrome compared with a population of healthy subjects. Nonrandomized, prospective, comparative case series. Twenty-six eyes of 13 patients with rosacea, 26 eyes of 13 patients with dry eye syndrome, and 24 eyes of 12 control subjects were included in this study. IC specimens were collected after clinical examination of the ocular surface and analyzed by flow cytometry, using antibodies directed to human lymphocyte antigen-DR (HLA-DR), intercellular adhesion molecule-1 (ICAM-1) (CD 54), and the peptidic core of the conjunctival mucin (M1/MUC5AC). The percentage of positive cells was calculated and levels of fluorescence expression quantified and compared with those obtained in a series of 12 healthy subjects. Tear break-up time (TBUT), Schirmer test, fluorescein and lissamin green stainings, and IC were realized in this study. A significant increase of HLA-DR and ICAM-1 expressions by epithelial cells was consistently found in the two pathologic groups compared with levels calculated in normal eyes. The two markers were well correlated with each other and inversely with TBUT and Schirmer test. The percentage of goblet cells was significantly decreased in rosacea patients and in dry eye patients compared with the normal group with a significant negative correlation with both HLA DR and ICAM-1 markers. Ocular rosacea and keratoconjunctivitis sicca were associated with severe ocular surface changes, such as an overexpression of inflammatory markers and a significant decrease in the number of goblet cells.